Experimental determination of residence time for sockeye salmon spawners on spawning grounds in the littoral zone of Lake Nachikinskoye (Kamchatka) - O. M. Zaporozhets; G. V. Zaporozhets (Известия ТИНРО, 2021)
Residence time of late-race sockeye spawners on spawning grounds located in the littoral zone of Lake Nachikinskoye in southern Kamchatka is determined directly using 11 series of tagging and tracking of tags conducted in 2018 and 2020 (700 tagged individuals). The residence time is the key parameter for calculation of the spawners number on the data of repeated observations from the beginning to the end of spawning. Methodology of the experiment is described in details and all data of measurements are presented. Impact of certain variables on the target function is discussed. The residence time is estimated as 5 days.